Psychological nursing intervention improve the mental health status of young patients with lung cancer surgery during the perioperative period. Issue 31 (6th August 2021) - Zhao, Li; Ma, Lina; Chen, Xiaomin; Liu, Zhuo
Abstract: Background: To explore the effects of psychological nursing on improving the mental health status of young patients with lung cancer surgery during the perioperative period. Methods: seventy-eight young patients (From February 2018 to February 2019) underwent lung cancer operation were selected. All these patients were randomly allocated to intervention group and control group. The patients in the control group were treated with general routine care. The patients in the intervention group were treated with a comprehensive and systematic family participation psychological nursing. The mental health status of the patients in the 2 groups were compared and analyzed. Results: The self-rating anxiety scale scores and self-rating depression scale scores of patients were significantly reduced in the intervention group compared with the control group ( P  < .05). The scores of somatization, obsessive symptoms, interpersonal relationship, depression, anxiety, hostile, phobic neurosis, stubborn, paranoia and psychosis were also significantly reduced in the intervention group compared with the control group ( P  < .05). Conclusion: the comprehensive and systematic psychological nursing intervention improved the mental health status of young patients with lung cancer surgery during the perioperative period.